2013
DOI: 10.1371/journal.pone.0080269
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive In Vivo Imaging of Near Infrared-labeled Transferrin in Breast Cancer Cells and Tumors Using Fluorescence Lifetime FRET

Abstract: The conjugation of anti-cancer drugs to endogenous ligands has proven to be an effective strategy to enhance their pharmacological selectivity and delivery towards neoplasic tissues. Since cell proliferation has a strong requirement for iron, cancer cells express high levels of transferrin receptors (TfnR), making its ligand, transferrin (Tfn), of great interest as a delivery agent for therapeutics. However, a critical gap exists in the ability to non-invasively determine whether drugs conjugated to Tfn are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
106
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 93 publications
(118 citation statements)
references
References 46 publications
10
106
0
Order By: Relevance
“…[31][32][33] This system has been designed to quantitatively image FRET donor fractions in vitro, ex vivo, and in vivo. 29,31,34 Briefly, the system uses a Maitai laser as a source and is coupled to a digital micromirror unit (DLP Discovery 4100 Kit and D2D module, Texas Instruments Inc., Dallas, Texas) to obtain a spatially controllable wide-field excitation [or active wide-field illumination (AWFI)]. The fluorescence signals are collected in transmittance geometry via an ultrafast-gated, intensified CCD (ICCD) camera (Picostar HR, LaVision GmbH, Goettingen, Germany) which has a 12-bit CCD and a resolution of 1376 × 1040 pixels.…”
Section: Time-domain Wide-field Gated Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…[31][32][33] This system has been designed to quantitatively image FRET donor fractions in vitro, ex vivo, and in vivo. 29,31,34 Briefly, the system uses a Maitai laser as a source and is coupled to a digital micromirror unit (DLP Discovery 4100 Kit and D2D module, Texas Instruments Inc., Dallas, Texas) to obtain a spatially controllable wide-field excitation [or active wide-field illumination (AWFI)]. The fluorescence signals are collected in transmittance geometry via an ultrafast-gated, intensified CCD (ICCD) camera (Picostar HR, LaVision GmbH, Goettingen, Germany) which has a 12-bit CCD and a resolution of 1376 × 1040 pixels.…”
Section: Time-domain Wide-field Gated Imagingmentioning
confidence: 99%
“…If the short-lifetime component is represented by τ 1 (FRET positive signals), then the parameter of particular interest is A 1 , as it represents the quenched fraction of the FRET donor, or in our application, the internalized amount of Tfn. 29,31,33,34 Here, human Tfn molecules labeled with a NIR FRET pair (Alexa Fluor 700-Alexa Fluor 750) were added to MadinDarby canine kidney (MDCK) cells and T47D cells (human ductal breast epithelial tumor cell line), both lines expressing human TfnR. 34,48,49 This specific FRET pair was chosen due to the significant spectral overlap and Forster distance (≈7.76 nm).…”
Section: Cell Assay Datamentioning
confidence: 99%
“…Similar compressive imaging work in FMT was reported later on by Ducros et al who used a wavelet base [5]. Beside validations in well-controlled settings, the method has been applied in vivo to quantify FRET signals [6], with applications in drug delivery monitoring [7].…”
Section: Introductionmentioning
confidence: 74%
“…In our previous work [16], we have demonstrated that this designed FRET NIR pair is able to discriminate the bound and internalized Tfn from free, soluble Tfn. We also have shown that the FD% indicates the fraction of intracellular receptor-bound Tfn, which includes receptor bound-Tfn at the plasma membrane as well as during clathrin-mediated internalization and subsequent endocytic recycling pathway back to the plasma membrane.…”
Section: Fret Analysis Of Ex Vivo Biodistributionmentioning
confidence: 96%
“…In our previous work [16], we have demonstrated that AF700-Tfn behaves as a FRET donor that can effectively transfer energy to AF750-Tfn acceptor molecules upon internalization of Tfn-transferrin receptor (Tfn-TfnR) complexes into cancer cells using FLIM. We also have shown that FD% levels, which are directly correlated to FRET efficiency, are positively dependent on A:D ratios and independent of acceptor levels upon Tfn-TfnR binding and internalization into cancer cells.…”
Section: Active Illumination For Ex Vivo Biodistributionmentioning
confidence: 99%